CRITICAL MANAGEMENT IN THE EVENTS OF INTERNATIONAL ORGANIZATION: MITIGATING HOTEL PRICE INCREASE OF 2024 MOTOGP - Karimafikri, Aisha Aulia; Vanindya Kusuma, Putu Adella; Saevasilvia, Saevasilvia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT Since Mandalika began hosting the MotoGP in 2022, the event has drawn a large number of visitors from various regions, showcasing significant potential for the local tourism industry. However, this success has been accompanied by challenges, particularly regarding hotel room rates that have far exceeded the limits established by the Governor of West Nusa Tenggara’s Regulation Number 9 of 2022, with prices rising as much as six to seven times. This steep increase has led to numerous complaints on social media, making it difficult for many attendees to find affordable accommodations. This study analyzes crisis management strategies related to hotel pricing in Mandalika during the 2024 MotoGP event, based on Coombs and Holladay’s crisis management theory, which includes three stages: pre-crisis, crisis, and post-crisis. The research follows a qualitative, case-study approach, using in-depth interviews with the Head of the Tourism Office as a key source of information. The results indicate that in the crisis stage, the sharp rise in hotel room prices—up to six to seven times the usual rates—caused significant public dissatisfaction on social media, emphasizing the need for regulatory review and stronger government action. In the post-crisis stage, this study suggests improved coordination between the government and hotel associations and recommends that visitors consider accommodations outside of Mandalika to reduce reliance on high-priced options. In conclusion, the study proposes stricter monitoring of hotel prices and increased collaboration across sectors to help maintain Mandalika positive image as a host for international events.